1984
DOI: 10.1177/154193128402800318
|View full text |Cite
|
Sign up to set email alerts
|

Feedback and Key Discrimination on Membrane Keypads

Abstract: This study investigated the effects of visual and tactile key discrimination and kinesthetic and auditory feedback on membrane keypads. More specifically, metal domes, embossed key edges and tone were examined. Fortyeight subjects were used in a 2 × 2 × 2 factorial design with two levels of key discrimination (with and without embossed key edges), two levels of kinesthetic feedback (with and without metal domes), and two levels of auditory feedback (with and without a 1000 Hz tone). Several types of preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Even with 2-key, users have to look at the screen to make a selection. A possible improvement could be to incorporate some kind of input feedback to let the user know what he or she is writing without looking at the television (Roe, Muto, & Blake, 1984). For instance, an option could be the remote or the television informing the user of the symbol written every time he or she writes something.…”
Section: Discussionmentioning
confidence: 98%
“…Even with 2-key, users have to look at the screen to make a selection. A possible improvement could be to incorporate some kind of input feedback to let the user know what he or she is writing without looking at the television (Roe, Muto, & Blake, 1984). For instance, an option could be the remote or the television informing the user of the symbol written every time he or she writes something.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies examined the addition of feedback to buttons on a flat surface that lacked the ability to travel downward [Fukumoto and Sugimura 2001;Lee and Zhai 2009;Leung et al 2007;Roe et al 1984;Rosenberg and Brave 1996]. The previous work on keyboard ergonomics covered buttons that could travel; however, these studies were limited to the constraints of mechanical designs [Clare 1976;Kinkead and Gonzalez 1969;Lewis et al 1997].…”
Section: Discussionmentioning
confidence: 98%
“…Typing speed decreases when buttons exist on a flat surface and do not travel, such as a touchscreen or a membrane keyboard [Cohen 1982;Pollard and Cooper 1979]. Roe et al [1984] found that adding audio feedback or tactile features to the flat surface could reduce this negative effect on typing performance.…”
Section: Typing On Flat Surfacesmentioning
confidence: 98%
“…He suggested efforts to evaluate keyboards requiring virtually no force and no displacement. Roe, Muto, and Blake (1984) described studies in which this hasbeen done. They investigated two levels each of kinesthetic (metal domes), tactile (embossed key boarders), and auditory (electronic tones) feedback in a full factorial design.…”
Section: Force·disp/acement Characteristicsmentioning
confidence: 99%